Perlindungan Hukum Terhadap Tanah Adat Terlantar Yang Belum Ditetapkan Sebagai Tanah Hak Pengelolaan Masyarakat Hukum Adat - Basar, Naomi Anastaria; Matuankotta, Jenny Kristiana; Uktolseja, Novyta (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2024)
Traditional land is land left by ancestors and is believed to have supernatural powers that are shared by a group of people. Abandoned land is land that is not cultivated or utilized. Based on article 8 letter a of Republic of Indonesia Government Regulation Number 20 of 2021 concerning controlling abandoned areas and land. Land with management rights that is excluded from the object of controlling abandoned land is land with management rights of indigenous communities. In this thesis, we examine customary land which is not the object of abandoned land, with the issues raised being the regulation of abandoned customary land in the Wermaktian sub-district, Rumsalut village and how to provide legal protection for abandoned customary land which has not been designated as the management right of customary law communities. This research uses a normative juridical method using a statutory approach, a conceptual approach and a case approach, as well as using primary, secondary and tertiary legal materials. The legal materials collected in the research are analyzed in a descriptive manner to draw conclusions. The results of this research show that regulations regarding abandoned customary land according to Law Number 5 of 1960 and Government Regulation of the Republic of Indonesia Number 20 of 2021 state that abandoned customary land in its regulation remains the management right of customary law communities. Then legal protection for abandoned customary land should be a form of protection for the dignity of customary law communities in accordance with the 1945 Constitution, article 18 b paragraph 2.